The Effect of using Incline Mat on the speed of Learning Forward Straddle Roll on Floor Exercises - Adel Jabbar Saeed; Ismail Ibraheem Mohameed (College of Physical Education and Sport Sciences, 2021)
The research aimed at using an incline mat to identify its effect on learning forward straddle roll. The researchers hypothesized significant differences between pre and post-tests in learning forward straddle roll. They used the experimental method on (34) sophomores from the college of physical education and sport sciences/university of Baghdad. The data was collected and treated using proper statistical operations to conclude that training aids have positive effects on learning forward straddle roll.